2019
DOI: 10.1002/ird.2374
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Controlled Drainage in Saline Vertisols of TBP Command Area of Karnataka, India

Abstract: Subsurface drainage (SSD) improves crop productivity in canal command areas suffering from waterlogging and salinity problems. However, excessive drainage of paddy fields under conventional SSD is known to cause irrigation water shortage during critical growth stages of rice and also results in excessive leaching of nitrogenous fertilizers particularly at the tail end of the irrigation command. To overcome these problems farmers of the Tungabhadra Project (TBP) irrigation command used to block the outlets of l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 10 publications
0
12
0
Order By: Relevance
“…The dimensions of the manhole/inspection chamber were 2 × 2 ×1.5 m (6 m³), and those of the guard wall were 2 × 0.6 ×1.8 m (2.16 m³). The inspection chamber was interconnected through a trench of collector drains and finally connected to the Nala /stream through an outlet under gravity flow (Karegoudar et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…The dimensions of the manhole/inspection chamber were 2 × 2 ×1.5 m (6 m³), and those of the guard wall were 2 × 0.6 ×1.8 m (2.16 m³). The inspection chamber was interconnected through a trench of collector drains and finally connected to the Nala /stream through an outlet under gravity flow (Karegoudar et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…The economics of these SSD systems were carried out in terms of total returns, cost of cultivation, net returns, net present value (NPV), benefit–cost ratio (BCR), internal rate of return (IRR) and payback period (Karegoudar et al, 2019; Raju et al, 2016) after the implementation of the drainage system over 30 years of life.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Man Singh et al (2002) [9] reported the highest (44.7 dS m -1 ) and lowest (3.86 dS m -1 ) mean salinity of drainage effluent at 35 and 15 m drain spacing areas which were in initial stage of reclamation. Whereas, Karegoudar et al (2019) [6] reported that the drain water salinity at 50 m drain spacing varied from [10] wherein the mean EC of majority of water samples of natural streams of LBMC in TBP command area were under category of C3 (EC 0.75 to 2.25 dS m -1 ) which indicate high salinity hazard and hence not feasible for irrigation. The canal water which passes through waterlogged saline soil and discharged into the natural stream (nala) would be of poor quality as it carries salts present in the soil profile.…”
Section: Electrical Conductivity (Ec)mentioning
confidence: 99%
“…DWM is gaining popularity in other countries of the world due to improved quality of water flowing from drained agricultural fields to surface water. The practice has been tested on research facilities in several countries including Lithuania [ 40 ], Sweden [ 41 ], Denmark [ 39 ], Italy [ 42 ], China [ 43 , 44 ], Iran [ 45 ], India [ 46 ], Japan [ 47 ], and Egypt [ 48 ]. Unfortunately, the results of experimental field studies usually include a short measurement period of CD effectiveness.…”
Section: Introductionmentioning
confidence: 99%